Implementasi Pembelajaran Sastra di Sekolah Dasar: Implementation of Literature Learning in Elementary Schools - Siti Arnisyah; Lastaria Lastaria; Husni Dwi Syafutri; Ilham Ilham (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research aims to analyze the application of literature learning in elementary schools in Central Kalimantan. This research method uses qualitative research methods to reveal the ways in which teachers implement literature learning in schools. The focus of this research is the suitability between the curriculum that applies in schools and the application of literature learning carried out by teachers. The results of this research show that overall literature learning is carried out in accordance with the curriculum guidelines applicable in schools according to the respondent's background. The results of this research show that students at grade 1 level do not have good abilities in appreciating, expressing and studying literary works. This is because at this level students are still in the learning stage of recognizing and writing letters or putting together words. However, at grade 3 and 4 students are able to appreciate, express and study literary works. Good language skills really support the implementation of learning in elementary schools.